High genetic diversity of immunity genes in an expanding population of a highly mobile carnivore, the grey wolf Canis lupus , in Central Europe - Hulva, Pavel; Kłodawska, Monika; Hájková, Andrea; Nowak, Sabina; Niedźwiedzka, Natalia; Biedrzycka, Aleksandra; Szewczyk, Maciej; Kloch, Agnieszka; Mysłajek, Robert; Jędrzejewska, Bogumiła (Diversity and Distributions, 2021)
Środki finansowe przyznane na realizację projektu w zakresie badań naukowych lub prac rozwojowych